Simulasi Kinerja AC Split Menggunakan R32, R410A, R290, dan R1234YF - Dwinanto, Matheus M. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2023)
Air conditioning (AC) is the treatment of air to regulate temperature, humidity, cleanliness and comfortable conditions needed by humans in a room. The lecture room in the Mechanical Engineering building at Nusa Cendana University is a building that is quite busy with lecture activities and services related to students. Therefore, it is necessary to have an air conditioning system to maintain thermal comfort for students and lecturers who carry out activities. This research aims to analyze the performance of the cooling system using refrigerants R290 and R1234YF as alternative refrigerants to replace refrigerants R32 and R410A using CoolTools software version 1.01. The simulation is based on steady state conditions with the AC cooling load being 5.3 kW. The results of this simulation show that the performance of an air conditioning system that uses R290 and R1234YF as an alternative refrigerant can be used because it has a better performance coefficient than refrigerants R32 and R410A